2010
DOI: 10.1088/0960-1317/20/10/105009
|View full text |Cite
|
Sign up to set email alerts
|

A micromirror module using a MEMS digital-to-analog converter and its application for optical surface profiling

Abstract: In this work, we develop a microelectromechanical digital-to-analog converter mirror module (M-DACMM) and demonstrate its application for non-contact optical surface profiling systems. The proposed device generates nano-scale step motions that are proportional to input digital signals. A fabrication process, which is capable of releasing a large-area movable mirror without etching holes, is proposed to realize the M-DACMM monolithically. The transient responses of the mirror module are also measured and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The system applies phase-shifting interferometry techniques [ 22 ], which require a movable reference mirror whose motion step is , where is the average wavelength of the photons emitted by the light source (tungsten-halogen lamp). The details of the system are presented in [ 16 ]. Because was approximately 570 nm, the motion step of the M-DAC device was designed to be 72 nm.…”
Section: Measurement and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system applies phase-shifting interferometry techniques [ 22 ], which require a movable reference mirror whose motion step is , where is the average wavelength of the photons emitted by the light source (tungsten-halogen lamp). The details of the system are presented in [ 16 ]. Because was approximately 570 nm, the motion step of the M-DAC device was designed to be 72 nm.…”
Section: Measurement and Discussionmentioning
confidence: 99%
“…These parameters are also indicated in the schematic shown in Figure 2 c. In addition, was designed to be 1.80 µm for the purposes of easy fabrication and low voltage actuation. The spring constants of the springs required for generating the desired motion steps ( i.e ., 72 nm) were evaluated using these parameters and the models described in [ 16 ]. Table 5 also lists these calculated spring constants.…”
Section: Measurement and Discussionmentioning
confidence: 99%
“…Comparing the speed of actuation to other electrostatic-actuated MEMS known from the literature, Grade et al [17] reported an electrostatic comb-drive actuator system with approx. the same travel range as presented here of 150 µm in less than 1 ms. By characterizing a DAC based on electrostatic parallel-plate actuation, Liao et al [6] reported a much smaller displacement of 1050 nm in less than 80 ms. During the experiment, system 1 in Figure 13a shows a total stroke of 149.5 ± 0.3 µm, with an average step size of 21.4 ± 6.1 µm at the control voltage of 60 V. Compared to the simulation, the displacement shows a slight deviation at the 011 and 100 positions. The DAC reaches a total displacement of 21.4 ± 1.5 µm, with an average step size of 3.1 ± 1.1 µm.…”
Section: Characterization Of the Combined Dac And Mechampmentioning
confidence: 99%
“…Comparing the speed of actuation to other electrostaticactuated MEMS known from the literature, Grade et al [17] reported an electrostatic combdrive actuator system with approx. the same travel range as presented here of 150 µm in less than 1 ms. By characterizing a DAC based on electrostatic parallel-plate actuation, Liao et al [6] reported a much smaller displacement of 1050 nm in less than 80 ms.…”
Section: Resonant Behavior Switching Speed and Reliability Of The Systemmentioning
confidence: 99%
See 1 more Smart Citation